Blockchain in Financial Services in Emerging Markets, Part II : Selected Regional Developments - Niforos, Marina (International Finance Corporation, Washington, DC, 2018)
Blockchain, or distributed ledger technology, is now disrupting the financial services industry as part of a larger wave of external innovations by digital financial technologies. Emerging markets, due to their higher banking risks, lower bank penetration, and greater presence of digital financing, are an ideal backdrop for the adoption of blockchain-based financial solutions, and benefits could include a technological leap forward and a boost to financial inclusion and growth. This note focuses on selected regions in emerging markets where distributed ledger technology is already affecting the provision of financial services, including Africa, Latin America, and Asia.